Expression and clinical significance of Sonic hedgehog in renal interstitial fibrosis of patients with diabetic kidney disease - HOU Shi-hui; LI Yi; GUAN Tao; LIU Jun-hui; ZHAO Jing-hong; HUANG Yunjian (Linchuang shenzangbing zazhi)
Objective To investigate the expression of Sonic hedgehog(Shh)in diabetic kidney disease(DKD)and its correlation to renal interstitial fibrosis.Methods Forty patients with DKD were enrolled and 12 confirmed normal renal tissues adjacent to the renal angiomyolipoma were assigned as control group.The clinical data of glycosylated hemoglobin(HbA1c),serum albumin(Alb),serum creatinine(SCr),blood urea nitrogen(BUN),24 h-urinary albumin(albuminuria)and estimated glomerular filtration rate(eGFR)by CKD-EPI equation were also collected.Masson staining was used to observe the morphology of renal tissues.According to the renal interstitial fibrosis and tubular atrophy(IFTA)scores,the tissues were divided into four groups:score 0,score 1,score2,and score 3.Human kidney biopsies samples were immunohistochemically stained with specific antibody against Shh protein andα-smooth muscle Actin(α-SMA)protein and then the correlation of Shh expression with clinicopathological parameters(HbA1c,serum creatinine,albuminuria,eGFR)was determined using statistical software SPSS 22.0.Results(1)Shh andα-SMA were rarely expressed in normal renal tissues.In DKD group,Shh was mainly expressed in renal tubular epithelialcells,especially in the proximal tubule,whileα-SMA was expressed in tubulointerstitium.As compared with the control group,the positive intensity of Shh andα-SMA in DKD group was increased significantly(P<0.05)and gradually with the increase in renal interstitial fibrosis pathological stage.(2)The positive intensity of Shh in renal tubular epithelial cells was positively correlated withα-SMA(r_s=0.82,P<0.001),HbA1c(r_s=0.54,P<0.001),serum creatinine(r_s=0.67,P<0.001)and24 h-urinary albumin(r_s=0.61,P<0.001),and negatively correlated with eGFR(r_s=-0.65,P<0.001).Conclusions Shh is highly expressed in renal tubular epithelial cells in patients with DKD,suggesting that Shh signal pathway is activated,which may be an important factor in the development of renal interstitial fibrosis in DKD.